2021
DOI: 10.3390/ani11123545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microencapsulated Methionine on Milk Production and Manure Nitrogen Excretions of Lactating Dairy Cows

Abstract: The study objective was to determine the effects of rumen-protected methionine (Met) by microencapsulation (RPM) on amino acid (AA) supply to the udder, milk production, and manure nitrogen (N) losses of dairy cows. A corn and soybean-based diet deficient in metabolizable Met (~10 g/d) was supplemented with RPM providing 0, 11.0, 19.3, and 27.5 g/d of Met. Dry matter intake (DMI), milk production, plasma essential AA (EAA), mammary plasma flow (MPF), and fecal (FN) and urinary N (UN) outputs (g/d) were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Nevertheless, MPE was similar at 24% ( p = 0.221) among treatments, suggesting that milk protein synthesis wouldn’t be a part of the improved N utilization efficiency. Although the TMR briquettes likely provide more metabolizable protein due to higher CP concentrations than CTL, potential limitations of individual essential amino acid supply for milk protein synthesis could hamper MPE [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, MPE was similar at 24% ( p = 0.221) among treatments, suggesting that milk protein synthesis wouldn’t be a part of the improved N utilization efficiency. Although the TMR briquettes likely provide more metabolizable protein due to higher CP concentrations than CTL, potential limitations of individual essential amino acid supply for milk protein synthesis could hamper MPE [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ile, Leu, Lys, Val, and His have the ability to enhance the transcription of β-casein synthesis by activating the mammalian target of rapamycin (mTOR) and the Ras/ERK signaling pathways, while the Arg signaling pathways can stimulate cell proliferation and enhance protein synthesis by activating the mTOR signaling pathway [16,53,54]. Additionally, Methionine serves as a precursor in the biosynthesis of nitric oxide, which enhances blood flow in the mammary glands [55]. The consumption of high-protein foods can elevate prolactin concentrations, and prolactin acts as a provider of amino acids through SNAT2 during the protein synthesis process in the mammary glands [14].…”
Section: Discussionmentioning
confidence: 99%
“…One of the proteins that has an important role is leucine; leucine plays a significant role in regulating the expression of SNAT2 in the mammary glands, as well as in the liver and adipose tissue, during lactation [51]. Meanwhile, King et al (2021) found that methionine supplementation may decrease milk protein synthesis but can enhance the availability of other amino acids to fulfill the body's needs [55]. Furthermore, methionine exhibits antioxidant properties that can mitigate the adverse effects of heavy metal exposure.…”
Section: Discussionmentioning
confidence: 99%
“…When the supply of Met to animals is insufficient, it will limit the synthesis of body proteins and cashmere fibre keratin, leading to the supply of an AA surplus relative to the requirement [3,4]. Furthermore, surplus AAs are catabolized in the liver, and their nitrogen (N) content is converted into urea, with a large proportion being excreted via urine [5]. The data from monogastric animals showed that insufficient Met in the diet can reduce the digestibility of protein in the small intestine and increase the faecal N output [6].…”
Section: Introductionmentioning
confidence: 99%